THE USE OF ASSISTIVE COUNSELLING TOOL “LUNG TB CARE” TO INCREASE PATIENT’S KNOWLEDGE LEVEL (A STUDY IN TUBERCULOSIS PATIENTS AT MALANG’S PRIMARY HEALTH CARE CENTERS) - Illahi, Ratna Kurnia; Pramestutie, Hananditia Rachma; Desyana, Made Shandra Dwi (International Journal of Pharmacy and Pharmaceutical Sciences, 2018)
Objective: Patient’s compliance in taking medication has an important role for the success of tuberculosis (TB) therapy because of long period of treatment. One of the reasons of frequent failure in tuberculosis therapy resulted from the lack of patient’s knowledge about the disease and treatment of tuberculosis, therefore affecting patient’s compliance. This study aimed to increase the knowledge level of tuberculosis patients. by using "Lung TB Care" as an assistive counselling tool in the form of computer applications that include pictures and information about the disease and treatment of tuberculosis. Methods: This study was a preliminary study with one-group retest design. The number of subjects in this study was 60 patients with the first category pulmonary TB. The Primary Health Care Centres were chosen with purposive sampling method, while the tuberculosis patients were chosen with random sampling according to appropriate inclusion and exclusion criteria. Results: The study indicated that there were changes in the level of patients’ knowledge, before and after counselling with “Lung TB Care”. The paired t-test analysis showed a significantly different result between two groups (p<0.001) regarding patient’s knowledge about the disease and treatment. Conclusion: To conclude this study, the use of assistive counselling tools “Lung TB Care” gives positive effect on the patients’ knowledge level, suggested that there are changes in the patients’ knowledge level after counselling by using assistive counselling tools.